2020
DOI: 10.1111/jon.12812
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Cerebral Glucose Metabolism during Dual‐Task Walking in Patients with Parkinson's disease

Abstract: BACKGROUND AND PURPOSE: Gait impairment is a hallmark of Parkinson's disease (PD). Natural walking involves more cognitive demand than treadmill walking or in-laboratory walking tests because patients have to actively work on navigation and top-down cognitive control which taxes cognitive reserve in the prefrontal cortex. To mimic the prefrontal engagement occurring with natural walking in a controlled and safe environment, dual-task (DT) treadmill walking has been developed. In this study, we tested the feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In a recent pilot study, we tested the feasibility of imaging the DT-walking-related changes in brain glucose metabolism in patients with PD (Szturm et al, 2020). Fifteen patients with PD (stage II and III) were scanned with FDG-PET.…”
Section: Anticipated and Preliminary Resultsmentioning
confidence: 99%
“…In a recent pilot study, we tested the feasibility of imaging the DT-walking-related changes in brain glucose metabolism in patients with PD (Szturm et al, 2020). Fifteen patients with PD (stage II and III) were scanned with FDG-PET.…”
Section: Anticipated and Preliminary Resultsmentioning
confidence: 99%
“…Similar fNIRS studies evaluating PD patients have reported no difference in PFC activation levels for DT-walking trials as compared to walk-only trials (Holtzer et al, 2015;Maidan et al, 2016;Liu et al, 2021). A recent positron emission tomography pilot study of DT-walking evaluated brain glucose metabolism in PD (Hoehn and Yahr stages 2 and 3) in ten patients who rested and five who conducted a DT treadmill/cognitive video game task during the uptake period (Szturm et al, 2020). DT interference (DTI) was consistently shown for gait and cognitive game performance measures for the DT-walking group.…”
Section: Introductionmentioning
confidence: 90%
“…Cortical areas devoted to visuospatial processing of behaviorally significant information, such as the PFC may be particularly susceptible to the neurodegenerative process in PD (Klencklen et al, 2012;Battisto et al, 2018;Lally et al, 2020). To overcome these limitations, Szturm et al (2017Szturm et al ( , 2020 developed a computer game-based rehabilitation treadmill platform (GRP; Mahana et al, 2021) which provides an integrated approach to assess and treat the decline in balance, gait, visuomotor, and executive cognitive functions. The GRP consists of a standard treadmill instrumented with a pressure mapping system used to compute spatiotemporal gait variables and gait stability measures (Szturm et al, 2017;Ahmadi et al, 2018Ahmadi et al, , 2019 and a computer display placed at the front of the treadmill for participants to view and interact with computer-generated activities while walking.…”
Section: Introductionmentioning
confidence: 99%
“…Patients in the early stages of PD have regional brain glucose hypometabolism, including the posterior temporoparietal, occipital, frontal, prefrontal, sensorimotor cortex and cerebellum putamen, pallidum, SNpc, and caudate [28,[84][85][86][87][88]. The treatment of PD patients modifies brain glucose consumption.…”
Section: Brain Glucose Metabolismmentioning
confidence: 99%